Developing a Mentoring Program for Shaping Students' Islamic Character - Suid Saidi; Dany Sulistiono; Abdul Holik Subaeri; Nadya Huda; M. Zainul; Abd. Haris (Nazhruna: Jurnal Pendidikan Islam, 2025)
This study aims to explore the implementation of the mentoring program at Madrasah Aliyah Negeri (MAN) 2 Kutai Kartanegara in shaping students' Islamic character. Using a qualitative case study approach, the research investigates the experiences, perceptions, and practices surrounding the program from the perspectives of students, mentors, and school administrators. Data were collected through semi-structured interviews, observations, and documentation over three months, from September to November 2024. The data analysis process involved transcribing interviews, organizing field notes, coding recurring themes, and interpreting the findings in relation to the research objectives. The findings reveal that the mentoring program at MAN 2 Kutai Kartanegara has significantly contributed to the development of students' Islamic character, promoting values such as honesty, discipline, respect, and responsibility. Mentors played a key role in fostering a supportive environment, helping students internalize these values through theoretical discussions and practical activities. While students demonstrated improvements in behavior and discipline, challenges such as time constraints, varying levels of religious knowledge, and limited parental involvement were noted as factors that hindered the full potential of the program. Recommendations for enhancing the program include allocating more time for mentoring, addressing the diverse religious backgrounds of students, and increasing parental involvement to reinforce the values taught in the program.